"Let's Try It!": Library Outreach in a Culture of Yes. Issue 1 (14th February 2018) - Owens, Tammi M.; Bishop, Katie
Abstract : Column description . The Marketing column features essays about a variety of creative and innovative marketing strategies used to highlight collections or promote services in all types of libraries. Its purpose is to provide real examples of how libraries are using marketing and outreach techniques in interesting ways. The column offers practical insight from libraries engaged with marketing. In addition to marketing, the column also features essays on successful programs and events that promote the library. Readers are invited to suggest topics or projects by contacting the column editor, Katy Kelly. Abstract : In the Research and Instruction Services department at the University of Nebraska at Omaha Libraries, a culture of yes drives our outreach efforts. This inclination to support non-traditional library services and events has allowed us to forge valued partnerships with student support services and learning communities, expanding the reach of the library into the university as a whole. In this column, we offer insight into how we have sustained a culture of yes as it relates to our student-focused outreach program. At the administrative level, defining the role of outreach for our organization and tying our outreach plan to the library's mission and strategic plan laid the groundwork for success. At the program level, we learned to articulate our intended outcomes and understand what success looks like. Our culture of yes embraces these successes along with any failures we have along the way. Moving forward, we continue to track and assess outreach and use each event or partnership to learn more about our students so that we may redesign our program according to lessons learned.